Love-themed Metaphors in the Lyrics of Caroline by MC Solaar - Laksman-Huntley, Myrna; Fadilah , Nadya (JURNAL ILMU BUDAYA, 2025)
In general, song lyrics are an expression of something that has been seen, heard or experienced by the songwriter. In addition, songwriters play with the words in order to appeal to their listeners. One approach to highlighting the uniqueness of the lyrics is the use of metaphors.